ANALYSIS OF THE ORGANIZATIONAL STRUCTURE AND PROCEDURES OF RESTAURANTS IN MINGA GUAZÚ - Micaela Insaurralde Romero, Jackelyn; Teresita Toledo Orzuza, Mariel (Revista Gênero e Interdisciplinaridade, 2023)
This study analyzes the organizational structure and operating procedures of restaurants. At the same time, the review of the literature develops relevant aspects for the design of an adequate structure, which allows the quality of the services offered by the gastronomic establishment. Likewise, the research has a mixed approach, being the level of the descriptive study and has as a data collection instrument the structured survey with closed and open alternatives applied to four restaurants in the urban center of the City of Minga Guazú. Likewise, an interview is carried out with the Owner-Manager of one of the restaurants, exposing the valuable information provided by his experience in the gastronomic field as Manager-owner. of the business. The results of the field work made it possible to show that an adequate organizational and procedural structure favors the quality of gastronomic services.